A retrospective study of neoadjuvant FOLFIRINOX in unresectable or borderline-resectable locally advanced pancreatic adenocarcinoma - Hosein Peter J; Macintyre Jessica; Kawamura Carolina; Maldonado Jennifer; Ernani Vinicius; Loaiza-Bonilla Arturo; Narayanan Govindarajan; Ribeiro Afonso; Portelance Lorraine; Merchan Jaime R; Levi Joe U; Rocha-Lima Caio M (BMC Cancer, 2012)
Abstract Background 5-fluorouracil, leucovorin, irinotecan and oxaliplatin (FOLFIRINOX) is superior to gemcitabine in patients with metastatic pancreatic cancer who have a good performance status. We investigated this combination as neoadjuvant therapy for locally advanced pancreatic cancer (LAPC). Methods In this retrospective series, we included patients with unresectable LAPC who received neoadjuvant FOLFIRINOX with growth factor support. The primary analysis endpoint was R0 resection rate. Results Eighteen treatment-naïve patients with unresectable or borderline resectable LAPC were treated with neoadjuvant FOLFIRINOX. The median age was 57.5 years and all had ECOG PS of 0 or 1. Eleven (61 %) had tumors in the head of the pancreas and 9 (50 %) had biliary stents placed prior to chemotherapy. A total of 146 cycles were administered with a median of 8 cycles (range 3-17) per patient. At maximum response or tolerability, 7 (39 %) were converted to resectability by radiological criteria; 5 had R0 resections, 1 had an R1 resection, and 1 had unresectable disease. Among the 11 patients who remained unresectable after FOLFIRINOX, 3 went on to have R0 resections after combined chemoradiotherapy, giving an overall R0 resection rate of 44 % (95 % CI 22–69 %). After a median follow-up of 13.4 months, the 1-year progression-free survival was 83 % (95 % CI 59-96 %) and the 1-year overall survival was 100 % (95 % CI 85-100 %). Grade 3/4 chemotherapy-related toxicities were neutropenia (22 %), neutropenic fever (17 %), thrombocytopenia (11 %), fatigue (11 %), and diarrhea (11 %). Common grade 1/2 toxicities were neutropenia (33 %), anemia (72 %), thrombocytopenia (44 %), fatigue (78 %), nausea (50 %), diarrhea (33 %) and neuropathy (33 %). Conclusions FOLFIRINOX followed by chemoradiotherapy is feasible as neoadjuvant therapy in patients with unresectable LAPC. The R0 resection rate of 44 % in this population is promising. Further studies are warranted.